Selections from Eliza Leslie - Leslie, Eliza, 1787-1858 (Legacies of nineteenth-century American women writers., 2011)
Best known for her culinary and domestic guides and the award-winning short story "Mrs. Washington Potts," Eliza Leslie deserves a much more prominent place in contemporary literary discussions of the nineteenth century. Her writing, known for its overtly moralistic and didactic tones-though often presented with wit and humor-also provides contemporary readers with a nuanced perspective for understanding the diversity among American women in Leslie's time.Leslie's writing serves as a commentary on gender ideals and consumerism; presents complicated constructions of racial, national, and class-